Durability and Mechanical Behavior of Fly Ash-GGBFS Geopolymer Concrete Utilizing Bottom Ash as Fine Aggregate. Issue 1 (2nd January 2019) - Ghosh, Rachit; Gupta, Sunil Kumar; Kumar, Anil; Kumar, Sanjay
ABSTRACT: The mechanical properties and durability parameters such as wet-dry cycles, water sorptivity, efflorescence and acid resistance of geopolymer concrete synthesized from fly ash of three different origins were evaluated. Scanning electron microscopy with energy dispersive X-ray spectroscopy and X-ray diffraction tests were conducted to examine the microstructure and mineralogical changes. It has been observed that the performance of geopolymer concrete containing fly ash with more glass content was better. The concrete samples were exposed to atmosphere for 180 days under a wide range of temperature (11o to 39oC) and relative humidity (42 to 82%). But the efflorescence was very low and the compressive strength deterioration was <10% from reference sample kept under controlled condition. This indicates good durability characteristic of fly ash based geopolymer concrete. GRAPHICAL ABSTRACT: